IMPROVEMENT OF LOW RANK COAL PROPERTIES BY VARIOUS UPGRADING PROCESSES - DATIN F. UMAR; BUKIN DAULAY (Indonesian Mining Journal, 2011)
A low rank coal from Banko, South Sumatera was used to study the properties improvement of the coal due to coal upgrading process. Various coal upgrading processes were conducted i.e. upgraded brown coal (UBC), hot water drying (HWD) and steam drying (SD). The UBC process was carried out in pilot scale with a capacity of 5 tons/day at temperature of 160°C and pressure of 0.35 MPa, while the HWD and SD pro- cesses were conducted in laboratory scale using autoclave at the temperature of 300ºC and pressure of about 12 MPa for 1 hour. The result indicates that the properties of Banko coals after the UBC, HWD and SD processes were improved. The calorific value of the upgraded coals was significantly increased in relevant to the decreasing of inherent moisture content and have better combustion characteristics than that of the raw coal. The highest calorific value can be achieved by SD process, followed by HWD and UBC processes.